Transcriptome Analysis of Cardiac Hypertrophic Growth in MYBPC3-Null Mice Suggests Early Responders in Hypertrophic Remodeling - Farrell, Emily; Armstrong, Annie E.; Grimes, Adrian C.; Naya, Francisco J.; de Lange, Willem J.; Ralphe, J. Carter (Frontiers in Physiology, 2018)
Rationale– With a prevalence of 1 in 200 individuals, hypertrophic cardiomyopathy (HCM) is thought to be the most common genetic cardiac disease, with potential outcomes that include severe hypertrophy, heart failure, and sudden cardiac death. Though much research has furthered our understanding of how HCM-causing mutations in genes such as cardiac myosin binding protein C (MYBPC3) impair contractile function, it remains unclear how such dysfunction leads to hypertrophy and/or arrhythmias, which comprise the HCM phenotype. Identification of early response mediators could provide rational therapeutic targets to reduce disease severity. Our goal was to differentiate physiologic and pathophysiologic hypertrophic growth responses and identify early genetic mediators in the development of cardiomegaly in the cardiac myosin binding protein C-null (cMyBP-C-/-) mouse model of HCM. Methods and Results- We performed microarray analysis on left ventricles of wild type (WT) and cMyBPC-/- mice (n=7 each) at postnatal day (PND) 1 and PND 9, before and after the appearance of an overt HCM phenotype. Applying the criteria of >2 fold change, we identified genes whose change was exclusive to pathophysiologic growth (n=61), physiologic growth (n=30), and genes whose expression changed >2 fold in both WT and cMyBP-C-/- hearts (n=130). Furthermore, we identified genes that were dysregulated in PND1 cMyBP-C-/- hearts prior to hypertrophy, including genes in mechanosensing pathways and potassium channels linked to arrhythmias. One gene of interest, Xirp2, and its protein product, are regulated during growth but also show early, robust prehypertrophic upregulation in cMyBP-C-/- hearts.. Additionally, the transcription factor Zbtb16 also shows prehypertrophic upregulation at both gene and protein levels. Conclusions– Our transcriptome analysis generated a comprehensive data set comparing physiologic versus hypertrophic growth in mice lacking cMyBP-C. It highlights the importance of extracellular matrix pathways in hypertrophic growth and early dysregulation of potassium channels. Prehypertrophic upregulation of Xirp2 in cMyBP-C-/- hearts supports a growing body of evidence suggesting Xirp2 has the capacity to elicit both hypertrophy and arrhythmias in HCM. Dysregulation of Xirp2, as well as Zbtb16, along with other genes associated with mechanosensing regions of the cardiomyocyte implicate stress-sensing in these regions as a potentially important early response in HCM.